Chromosome Research - Chromosome Research (Springer Nature, 2026)
Chromosome Research is a leading journal in chromosome, chromatin, and nuclear biology, publishing high-quality experimental studies across all organisms. Topics include chromosome organization, chromatin biology, DNA repair, epigenetics, cancer cytogenomics, and comparative genomics. With no citation limits and an average first decision time of just 4 days, the journal ensures rapid, rigorous review.
FI 0.56
Q3
Keywords: Life Sciences; Cell & Molecular Biology; Biología celular; Biología molecular; Acuerdos transformativos; Transformative agreements; Organización cromosómica; Biología de la cromatina; Reparación del ADN